3 The Revised Statutes, Code, and General Laws of the State of New York 3330, § 1 (Clarence F. Birdseye ed., 1890) - (:unkn) unknown (My University, 1890)
Prohibited the manufacture, sale, giving, keeping for sale, or disposition of any slungshot, billy, sand-club, or metal knuckles. Also prohibited the sale of pistols to minors in any city or incorproated village without written consent from a magistrate.
Keywords: POSSESSION - NON-GUN ARMS; TRANSFER - MINORS